Highlighting short-lived excited electronic states with pump-degenerate-four-wave-mixing - Marek, Marie Sophie; Buckup, Tiago; Southall, June; Cogdell, Richard J.; Motzkus, Marcus (The journal of chemical physics, 2013)
Detection of short-lived transient species is a major challenge in femtosecond spectroscopy, especially when third-order techniques like transient absorption are used. Higher order methods employ additional interactions between light and matter to highlight such transient species. In this work we address numerically and experimentally the detection of ultrafast species with pump-Degenerate Four Wave Mixing (pump-DFWM). In this respect, conclusive identification of ultrafast species requires the proper determination of time-zero between all four laser pulses (pump pulse and the DFWM sequence). This is addressed here under the light of experimental parameters as well as molecular properties: The role of pulse durations, amount of pulse chirp as well as excited state life time is investigated by measuring a row of natural pigments differing mainly in the number of conjugated double bonds (N = 9 to 13). A comparison of the different signals reveals a strikingly unusual behavior of spheroidene (N = 10). Complete analysis of the pump-DFWM signal illustrates the power of the method and clearly assigns the uniqueness of spheroidene to a mixing of the initially excited state with a dark excited electronic state.
Gesehen am 22.06.2021